Modern Strategies for Enhancing Screening Efficiency and Treatment Processes for Cervical Cancer: A Narrative Review - Zhumabekova, Altynai (Asian Journal of Pharmaceutics (AJP), 2024)
Cytological screening plays a crucial role in reducing the incidence of cervical cancer in affluent countries. Determining the optimal approach for treating cervical cancer is critical before implementation. Chemotherapy can be administered as an adjuvant or as a standalone treatment. For patients with International Federation of Obstetrics and Gynecology stage IB1-IIA1 cervical cancer, type IIB, or C1 extended hysterectomy is typically recommended. Although surgery is an option, it increases the likelihood of morbidity and negatively affects patients’ quality of life (QoL). The primary objective of this review was to evaluate the current methods and programs for screening and treating cervical cancer at various stages, including early, locally advanced, and advanced stages. Human papillomavirus screening is a reliable method for detecting cervical cancer in women at an early stage and offers better results than cytological testing. The screening frequency, due to the varying intervals implemented by different countries, ranges from annually to once every 5–10 years. Self-sampling can improve cervical cancer screening by providing convenience, and offering various testing options may encourage individuals who have not yet been screened. Early cancer detection programs, innovative screening initiatives, and improved accessibility and quality of treatment are crucial to improving oncological care. In addition, training oncologists, promoting a healthy lifestyle through interagency collaboration, and establishing a registry for chancery cases can help enhance the QoL.